2022
DOI: 10.1001/jamapsychiatry.2022.0799
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness Abnormalities at Different Stages of the Illness Course in Schizophrenia

Abstract: IMPORTANCE Questions of whether and how cortical thickness (CTh) alterations differ over the course of schizophrenia (SCZ) have yet to be resolved. OBJECTIVE To characterize CTh alterations across illness stages in SCZ.DATA SOURCES PubMed, Embase, Web of Science, and Science Direct were screened for CTh studies published before June 15, 2021.STUDY SELECTION Original studies comparing whole-brain CTh alterations from healthy controls in individuals at clinical high-risk (CHR), first episode of psychosis (FEP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 81 publications
6
43
0
Order By: Relevance
“…Thus, brain structure can provide more stable and reliable clustering solutions. Further, aberrant cortical thickness has been reported in various illness stages of schizophrenia (Zhao et al, 2022), and has been found to track the inter-individual differences in psychotic symptoms (Oertel-Knöchel et al, 2013) and Thought and Language Disorder scores in schizophrenia (Palaniyappan et al, 2020). Prior cluster analytic studies have uncovered a consistent cluster of patients with generalized reduction in cortical thickness (Dwyer et al, 2018;Chand et al, 2020;Liang et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, brain structure can provide more stable and reliable clustering solutions. Further, aberrant cortical thickness has been reported in various illness stages of schizophrenia (Zhao et al, 2022), and has been found to track the inter-individual differences in psychotic symptoms (Oertel-Knöchel et al, 2013) and Thought and Language Disorder scores in schizophrenia (Palaniyappan et al, 2020). Prior cluster analytic studies have uncovered a consistent cluster of patients with generalized reduction in cortical thickness (Dwyer et al, 2018;Chand et al, 2020;Liang et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…The current study extends our understanding of the role of brain morphometry for psychosis by showing that regional neuroanatomical variation in CHR-P individuals is nested within normative variation. A small minority of CHR-PC patients had pronounced decrements in the cortical thickness and surface area of temporal regions reinforcing the relevance of these regions for psychosis risk [7][8][9] and syndromal schizophrenia. 11,12,23 Regional deviation from normative patterns in the CHR-P individuals did not show meaningful associations with the severity of positive symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…6 Multiple magnetic resonance imaging (MRI) studies have focused on identifying neuroanatomical alterations in CHR-P compared to healthy individuals (HI). Two metaanalyses of these studies have highlighted cortical thickness (CT) reductions of small effect size in the frontotemporal regions of CHR individuals 7,8 while a mega-analysis of brain morphometric data from 1792 CHR-P and 1377 HI from the CHR-P Working Group of the Enhancing Neuroimaging Genetics through Meta-analysis (ENIGMA) Consortium found that such CT reductions were widespread (Cohen d range of -0.17 to -0.09). 9 Recently psychiatric neuroimaging has turned to normative modeling, which quantifies individual-level deviation in brain-derived phenotypes relative to a normative reference population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the thickness of the cortex, the densities of cells within the cortical laminar are also important and thought to impact brain function. For example, changes in cortical thickness and cell density have been reported in several neurological disorders (Cotter et al, 2001; Hanford et al, 2016; Thu et al, 2010; Zhao et al, 2022). However, little is known about the variability of cell densities within a gyrus/sulcus and how it is determined.…”
Section: Resultsmentioning
confidence: 99%